2012
DOI: 10.2147/opth.s29718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photodynamic therapy (PDT), posterior subtenon injection of triamcinolone acetonide with PDT, and intravitreal injection of ranibizumab with PDT for retinal angiomatous proliferation

Abstract: BackgroundThe purpose of this work was to compare the efficacy of photodynamic therapy (PDT) with or without posterior subtenon injections of triamcinolone acetonide (STA) or intravitreal injections of ranibizumab (IVR) for retinal angiomatous proliferation (RAP).MethodsThirty-seven eyes from 33 consecutive patients with RAP were treated by PDT monotherapy (Group 1), PDT combined with STA (Group 2), or PDT combined with IVR (Group 3). The best-corrected visual acuity, greatest linear dimension, central retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The results are in agreement with the results reported in a number of studies on ranibizumab in monotherapy 18 20 , 27 or in combination with PDT. 24 , 28 , 29 In this sense, the observed functional improvement (VA) proved greater for the combination of ranibizumab plus PDT with verteporfin, while from the anatomical perspective (foveal thickness), the greatest reduction corresponded to the group administered ranibizumab in monotherapy. This finding differs from the observations of other studies in which functional and anatomical improvement showed the same trend.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in agreement with the results reported in a number of studies on ranibizumab in monotherapy 18 20 , 27 or in combination with PDT. 24 , 28 , 29 In this sense, the observed functional improvement (VA) proved greater for the combination of ranibizumab plus PDT with verteporfin, while from the anatomical perspective (foveal thickness), the greatest reduction corresponded to the group administered ranibizumab in monotherapy. This finding differs from the observations of other studies in which functional and anatomical improvement showed the same trend.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 34 included studies, 24 reported on anti-VEGF therapy alone ( Engelbert et al, 2009 ; Montero et al, 2009 ; Atmani et al, 2010 ; Hemeida et al, 2010 ; Reche-Frutos et al, 2011 ; Parodi et al, 2013 ; Gharbiya et al, 2014 ; Inoue et al, 2014 ; Shin and Yu, 2014 ; Park and Roh, 2015 ; Cho et al, 2016 ; Matsumoto et al, 2016 ; Kim et al, 2017a ; Kim et al, 2017b ; Hata et al, 2017 ; Kim et al, 2018 ; Browning et al, 2019 ; Invernizzi et al, 2019 ; Kim et al, 2019 ; Maruyama-Inoue et al, 2019 ; Arias et al, 2020 ; Ernest et al, 2020 ; Kim, 2020 ; Kim et al, 2020 ), 8 reported on anti-VEGF therapy combined with PDT ( Saito et al, 2010 ; Lee et al, 2011 ; Nakano et al, 2012 ; Saito et al, 2012 ; Saito et al, 2013 ; Seidel et al, 2013 ; Saito et al, 2016 ; Malamos et al, 2018 ) and 2 studies compared anti-VEGF therapy alone versus combined with PDT. ( Rouvas et al, 2012 ; Arias et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Publication year ranged from 2010 to 2018. Of these 10 studies, 5 were retrospective ( Saito et al, 2010 ; Nakano et al, 2012 ; Saito et al, 2012 ; Saito et al, 2013 ; Saito et al, 2016 ), 3 were prospective ( Lee et al, 2011 ; Seidel et al, 2013 ; Malamos et al, 2018 ) and two were randomized trials. ( Rouvas et al, 2012 ; Arias et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of documented studies have recommended the application of intravitreal injection of anti-VEGF drug for treating RAP, which was considered as a form of exudative AMD [ 17 19 ]. Since inflammation was involved in the pathogenesis of RAP, recent research studies have shown the efficacy of intravitreal or periocular TA injection in the treatment of RAP [ 20 , 21 ]. In this case, the patient only received antibiotic and triamcinolone therapy in the early stage due to the severe systemic inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%